The Genetics of Axon Guidance and Axon Regeneration in Caenorhabditis elegans. Issue 3 (1st November 2016) - Chisholm, Andrew D; Hutter, Harald; Jin, Yishi; Wadsworth, William G
Abstract: The correct wiring of neuronal circuits depends on outgrowth and guidance of neuronal processes during development. In the past two decades, great progress has been made in understanding the molecular basis of axon outgrowth and guidance. Genetic analysis in Caenorhabditis elegans has played a key role in elucidating conserved pathways regulating axon guidance, including Netrin signaling, the slit Slit/Robo pathway, Wnt signaling, and others. Axon guidance factors were first identified by screens for mutations affecting animal behavior, and by direct visual screens for axon guidance defects. Genetic analysis of these pathways has revealed the complex and combinatorial nature of guidance cues, and has delineated how cues guide growth cones via receptor activity and cytoskeletal rearrangement. Several axon guidance pathways also affect directed migrations of non-neuronal cells in C. elegans, with implications for normal and pathological cell migrations in situations such as tumor metastasis. The small number of neurons and highly stereotyped axonal architecture of the C. elegans nervous system allow analysis of axon guidance at the level of single identified axons, and permit in vivo tests of prevailing models of axon guidance. C. elegans axons also have a robust capacity to undergo regenerative regrowth after precise laser injury (axotomy). Although such axon regrowth shares some similarities with developmental axon outgrowth, screens for regrowth mutants have revealed regeneration-specific pathways and factors that were not identified in developmental screens. Several areas remain poorly understood, including how major axon tracts are formed in the embryo, and the function of axon regeneration in the natural environment.